Compliance with Standard Precautions and Associated Factors among Healthcare Workers in Gondar University Comprehensive Specialized Hospital, Northwest Ethiopia. (16th January 2017) - Haile, Tariku Gebre; Engeda, Eshetu Haileselassie; Abdo, Abdella Amano
Abstract : Background . In many studies, compliance with standard precautions among healthcare workers was reported to be inadequate. Objective. The aim of this study was to assess compliance with standard precautions and associated factors among healthcare workers in northwest Ethiopia. Methods. An institution-based cross-sectional study was conducted from March 01 to April 30, 2014. Simple random sampling technique was used to select participants. Data were entered into Epi info 3.5.1 and were exported to SPSS version 20.0 for statistical analysis. Multivariate logistic regression analyses were computed and adjusted odds ratio with 95% confidence interval was calculated to identify associated factors. Results. The proportion of healthcare workers who always comply with standard precautions was found to be 12%. Being a female healthcare worker (AOR [95% CI] 2.18 [1.12–4.23]), higher infection risk perception (AOR [95% CI] 3.46 [1.67–7.18]), training on standard precautions (AOR [95% CI] 2.90 [1.20–7.02]), accessibility of personal protective equipment (AOR [95% CI] 2.87 [1.41–5.86]), and management support (AOR [95% CI] 2.23 [1.11–4.53]) were found to be statistically significant. Conclusion and Recommendation. Compliance with standard precautions among the healthcare workers is very low. Interventions which include training of healthcare workers on standard precautions and consistent management support are recommended.